RET Inhibitor SPP86 Triggers Apoptosis and Activates the DNA Damage Response Through the Suppression of Autophagy and the PI3K/AKT Signaling Pathway in Melanoma Cells - Zhang Y; Liu H; Wang K; Zheng J; Luan H; Xin M (Drug Design, Development and Therapy)
Yuli Zhang,1,2 Haidong Liu,1 Kun Wang,3 Juan Zheng,4 Hong Luan,1 Ming Xin5 1Department of Dermatology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China; 2Department of Endocrinology, The Second Hospital of Shandong University, Jinan, Shandong, People’s Republic of China; 3Department of Endocrinology and Metabology, Liaocheng People’s Hospital, Liaocheng, Liaocheng, Shandong, People’s Republic of China; 4Joint Laboratory for Translational Medicine Research, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China; 5The Key Laboratory of Molecular Pharmacology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of ChinaCorrespondence: Ming Xin, The Key Laboratory of Molecular Pharmacology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China, Email xinming137@163.com Hong Luan, Department of Dermatology, Liaocheng People’s Hospital, Liaocheng, Shandong, People’s Republic of China, Email lcsrmyy@126.comBackground: Melanoma is a highly lethal form of skin cancer, and effective treatment remains a significant challenge. SPP86 is a novel potential therapeutic drug. Nonetheless, the specific influence of SPP86 on autophagy, particularly its mechanisms in the context of DNA damage and apoptosis in human melanoma cells, remains inadequately understood. Thus, this study aims to explore the effects of SPP86 on autophagy and to elucidate its association with cell proliferation, apoptosis, and DNA damage in melanoma cells.Methods: This study assessed the anti-tumor effects of SPP86 on cell viability, colony formation, apoptosis, and DNA damage in two melanoma cell lines, A375 and A2058. Concurrently, the underlying mechanisms, including the PI3K/AKT signaling pathway and autophagy modulation, were also elucidated.Results: The study demonstrated that SPP86 exerts anti-tumor effects in melanoma cells through multiple mechanisms: it induces apoptosis, causes DNA damage, inhibits cell proliferation, and suppresses the PI3K/AKT signaling pathway. Importantly, the inhibition of autophagy appears to be a critical component of SPP86’ s mode of action, with the modulation of autophagic processes influencing the cytotoxicity against melanoma cells.Conclusion: These promising findings suggest that SPP86 is a potential drug candidate for the treatment of melanoma, warranting further research and development.Keywords: melanoma, SPP86, autophagy, DNA damage, apoptosis, PI3k/AKT